الأسماك ومنتجاتها في خرسون البيزنطية: منذ القرن السادس حتى القرن العاشر الميلاديين - خلف، محمد إبراهيم محمد Khalaf, Mohammed Ibrahim Mohammed (جامعة أسيوط - كلية الآداب, 2022)
يلقي هذا البحث الضوء على الأسماك ومنتجاتها، التي مثلت دورا مهما في اقتصاد مدينة خرسون البيزنطية، منذ القرن السادس حتى القرن العاشر الميلاديين. وهذه المدينة من المدن الرئيسة للإمبراطورية البيزنطية في شبه جزيرة القرم؛ نظرا لأهميتها السياسية والتجارية. ولا شك أن الأسماك ومنتجاتها لعبت دورا مهما في اقتصاد خرسون؛ لما لها من قيمة اقتصادية عالية وزيادة الطلب عليها؛ ولذلك كانت من السلع الأساسية في التجارة العالمية، وكان إنتاجه من أولى الصناعات في خرسون. This paper discusses the fish and its products that had played an influential role in Cherson’s economy, from the 6th to the 10th Centuries. Cherson was considered one of the main cities of the Byzantine Empire in the Crimean Peninsula, given its commercial and political importance. Fisheries and its products had undoubtedly played an influential role in developing Cher-son’s economy due to their great economic value and increasing world demand. Therefore, they became the first essential com-modities in international trade. Fisheries were primarily industrial production in Cherson.
Keywords: التاريخ الاقتصاد -- الثروة السمكية -- خرسون -- الإمبراطورية البيزنيطية